All in the family : Latin America's most important international financial flow : report (Inter-American Dialogue WashingtonUS, 2004)
Identifies and analyzes the policy challenges that large and growing remittance flows posed for Latin American and Caribbean governments, the US government and international financial institutions.
Keywords: REMITTANCES